(untitled) (Research, Society and Development, 2021)
The present study aimed to assess handgrip strength, nutritional status and its relationship with functional limitations in the elderly. A cross-sectional, quantitative study with a sample of 60 elderly women> 60 years old, carried out at the Centro de Convivência Dos Idosos, located in the city of Northeast Brazilian. Variables were studied to assess body composition. Food consumption was assessed using the Food Frequency Questionnaire (FFQ) adapted for the elderly. The Palmar Grip Force (FPP) data were evaluated using the formula. For significant differences, p <0.05 was adopted. The research received ethical approval with opinion number 3,248,005. The mean age of the final sample was 67.92 ± 7.77. There was a prevalence of overweight (45%) according to BMI. Caloric intake was above the recommendation (1907.38 ± 783.07). Participants aged 60 to 69 years old, the means for both FPP-D (26.70 + 2.37) and FPP-ND (25.23 + 1.73) were adequate, among those who aged over 70 years, the mean FFP-ND (18.93 + 3.55) was below expectations, with only the FPP-D value (20.53 + 3.73) being adequate. The results obtained in this study suggest that the muscle strength of the elderly is preserved, which influences the functional performance of this population. The inadequate nutritional status of overweight women in this study is the result of consuming foods with high caloric density and low quality of macro and micronutrients.